Assessing The Legal Position of Intellectual Property Rights in Artificial Intelligence Works - Wiwin; Aditya, Muhammad; Ramadhani, Riska; Syahril, Muh. Akbar Fhad (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
The development of AI usage raises legal challenges in the protection of intellectual property rights (IPR). One crucial issue is copyright over AI-created works, reflected in various lawsuits in United States and viral case in Indonesia regarding AI altering personal photos in the style of Ghibli anime. This study analyzes: (1)The position of AI as a creator; (2)The position of AI users as creators; and (3)The legal status of AI-produced works. Normative methods used with legislative, analytical, and conceptual approaches. The results show that AI cannot be considered a creator because it does not meet the requirements for a legal subject (intellectuality and legal responsibility), instead AI only seen as a legal object in Indonesia. Additionally, AI users are also not recognized as creators because they do not meet the criteria for originality, fixation, and IPR protection. Therefore, AI works are categorized as being in the public domain.